Sources of the Encyclical "Ut unum sint" - Přibyl, Stanislav 1966- (2022)
John Paul II’s encyclical Ut unum sint on commitment to ecumenism was published 30 years after the ground-breaking ecumenism decree of Vatican II Unitatis redintegratio. It was meant to present a summary of everything the Catholic Church and its partners achieved in the field of ecumenical efforts. However, the article does not list these achievements but discusses the very fundamentals of Catholic identity, namely, how the Catholic Church is to remain faithful to itself in developing ecumenical dialogue with other churches and ecclesial communities. The article thus provides a detailed analysis of the way the encyclical uses the basic sources of faith, that is, the logia of the Sacred Scripture, Church Fathers and the Magisterium. As one might expect, the documents of the Magisterium that are quoted are the documents of Vatican II because this council represents a real turning point in the relations of the Catholic Church towards ecumenism. The article also considers the role of the canon law for ecumenism because both codices of canon law as well as the ecumenical directory represent major tools for the realisation of ecumenical efforts.
Keywords: Catholic Church; Catholic Faith; Code of Canon Law; Holy Scripture; Orthodox Churches; Protestant Reformation; Tradition; Ecumenical Dialogue; encyclical; Magisterium; Papacy